2007
DOI: 10.1021/ja068909q
|View full text |Cite
|
Sign up to set email alerts
|

Geminate Charge Recombination in Alternating Polyfluorene Copolymer/Fullerene Blends

Abstract: By measuring excited state and charge dynamics in blends of an alternating polyfluorene copolymer and fullerene derivative over nine orders in time and two orders in light intensity, we have monitored the light-induced processes from ultrafast charge photogeneration to much slower decay of charges by recombination. We find that at low light intensities relevant to solar cell operation relatively fast (approximately 30 ns) geminate recombination is the dominating charge decay process, while nongeminate recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
242
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(274 citation statements)
references
References 45 publications
29
242
3
Order By: Relevance
“…Time scales of hundreds of picoseconds to nanoseconds have been reported for this process in various polymers. [9][10][11]13,17,41 We are not able to distinguish charges that are bound in the CT state from free ones using the broad polaron absorption band (similar spectral signatures have also been noted in TA studies of some other polymers). 9,10 On the basis of a model by Laquai et al, 9−11 both are expected even at the earliest time delays, since they are instantaneously generated and do not interconvert.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Time scales of hundreds of picoseconds to nanoseconds have been reported for this process in various polymers. [9][10][11]13,17,41 We are not able to distinguish charges that are bound in the CT state from free ones using the broad polaron absorption band (similar spectral signatures have also been noted in TA studies of some other polymers). 9,10 On the basis of a model by Laquai et al, 9−11 both are expected even at the earliest time delays, since they are instantaneously generated and do not interconvert.…”
mentioning
confidence: 55%
“…A similar flat band extending next to the GSB with a peak at lower wavelengths has been observed in blends of other donor− acceptor copolymers with PCBM, and was also assigned to the charged polymer. 9,17 The anion of PCBM is known to absorb in the 1030 nm region, and is thus outside our measuring window. 13 It has often been reported that CS occurs quantitatively in less that 100 fs in polymer:fullerene bulk heterojunctions.…”
mentioning
confidence: 99%
“…51 However, they were not able to determine whether the product of the charge transfer was bound CT states or free charge carriers. De et al 52 and Hwang et al 53 were among the first to be able to determine ultrafast free charge carrier generation in polymer:fullerene blends using TA measurements in the subnanosecond time regime. Both of them observed the generation of free carriers within ~ 200 ps.…”
Section: Ultrafast Generation Of Free Charge Carriersmentioning
confidence: 99%
“…11 In most organic donor/acceptor systems the geminate processes should be present to some degree and will have to be considered, relative to other types of recombination.…”
Section: Introduction a Backgroundmentioning
confidence: 99%